An overview: exploring the potential of fruit and vegetable waste and by-products in food biodegradable packaging - Ali, Muhammad Qasim; Noormazlinah, Ahmad; Mohd Akmal, Azhar; Mimi Sakinah, Abdul Munaim; Hussain, Ashiq; Ali Mahdi, Amer (Springer Nature, 2024)
Food waste and by-products negatively impact the environment, economy, and society. One solution to this issue is repurposing this waste by creating food packaging materials. Packaging is safe for food, but using non-biodegradable materials, including microplastics, has led to pollution. The food industry generates substantial amounts of waste that creates environmental concerns. Edible and functional food packaging, crafted from food waste and natural materials, presents a sustainable approach by reducing waste and plastic usage. These edible materials are consumed with food, reducing disposal and environmental impact. This manuscript explores the potential uses of biopolymers, packaging, and edible films and coatings As alternatives to traditional food packaging. By-products of fruits are valuable food waste, often discarded despite containing beneficial compounds like polyphenols, vitamins, and minerals. This review focuses on recent research using vegetable and fruit waste to improve packaging systems, antioxidant, physical, and mechanical properties, and antimicrobial features; advancements in synthetic and biobased films enhanced with by-product compounds; and their role in biodegradable food packaging.